The effects of teleconnections on water and carbon fluxes in the two South America’s largest biomes - Edivaldo A. O. Serrão; Rosane B. L. Cavalcante; Paulo R. Zanin; Renata G. Tedeschi; Thomas R. Ferreira; Paulo R. M. Pontes (Scientific Reports)
Abstract Ecosystem services provided by terrestrial biomes, such as moisture recycling and carbon assimilation, are crucial components of the water, energy, and biogeochemical cycles. These biophysical processes are influenced by climate variability driven by distant ocean-atmosphere interactions, commonly referred to as teleconnections. This study aims to identify which teleconnections most significantly affect key biophysical processes in South America’s two largest biomes: The Amazon and Cerrado. Using 20 years of monthly data on Precipitation (P), Evapotranspiration (ET), Gross Primary Productivity (GPP), and Ecosystem Water Use Efficiency (EWUE), alongside data from six teleconnections (Antarctic Oscillation - AAO, Atlantic Multidecadal Oscillation - AMO, Oceanic Niño Index - ONI, Atlantic Meridional Mode - AMM, North Atlantic Oscillation - NAO, and Pacific Decadal Oscillation - PDO), we developed a multivariate linear model to assess the relative importance of each teleconnection. Additionally, time-lagged Spearman correlations were used to explore relationships between biophysical variables and teleconnections. Our findings indicate that the AMO exerts the strongest influence across all studied variables. Furthermore, ONI and AMM significantly impact precipitation in the northern Amazon, with a 3-month lag in ONI showing positive correlations with ET and GPP. In contrast, a 3-month lag in AMO negatively influences GPP in the southern Amazon and Cerrado, though positive correlations with EWUE were observed in the same region. These insights highlight the complex and regionally varied impacts of teleconnections on South America’s largest biomes.